2005
DOI: 10.1158/0008-5472.can-04-4486
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein α Knock-in Mice Exhibit Early Liver Glycogen Storage and Reduced Susceptibility to Hepatocellular Carcinoma

Abstract: The CCAAT/enhancer binding protein A (C/EBPA) is vital for establishing normal hepatic energy homeostasis and moderating hepatocellular growth. CEBPA loss-of-function mutations identified in acute myeloid leukemia patients support a tumor suppressor role for C/EBPA. Recent work showed reductions of C/EBPA levels in human hepatocellular carcinoma with the reductions correlating to tumor size and progression. We investigated the potential of reactivating c/ebpa expression during hepatic carcinogenesis to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 32 publications
2
65
0
Order By: Relevance
“…C/EBPα is a major player in hematopoietic differentiation, and its involvement in hematologic malignancies is very well documented (37,38). It also has been described as a tumor suppressor in lung and liver tumors (39,40). The function of C/EBPβ in tumorigenesis is less investigated (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPα is a major player in hematopoietic differentiation, and its involvement in hematologic malignancies is very well documented (37,38). It also has been described as a tumor suppressor in lung and liver tumors (39,40). The function of C/EBPβ in tumorigenesis is less investigated (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Liver tumors were induced by DEN/PB tumor liver induction protocol as described (8). 5 μg DEN/g body weight was injected into WT and S193D mice, and then mice were provided with PB (0.05%) in drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…Given the strong inhibition of liver proliferation after PH in S193D knockin mice, we expected that these animals should be resistant to the development of tumors. To test this suggestion, we applied DEN/PB tumor liver induction protocol (8). We surprisingly found that the S193D mice developed tumors much earlier than WT mice ( Figure 3A).…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations